FACTORS THAT IMPACT PARENTAL SUCCESS IN SUPPORTING CHILDERN’S DISTANCE LEARNING - Nikolaeva, Elena; Dunaevskaya, Elvira; Kalabina, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Distance learning unexpectedly arrived to Russian schools in March 2020, schools and teachers were not ready for this training type. The aim of present paper is to collect and evaluate parents’ view on family preparedness to distance education and on parents’ and children’ coping with school assignments during the lockdown. 304 parents were interviewed. The data provide evidence that the higher level of parental education is a factor in the efficient distance learning of their children. The higher level of parental education correlates with fewer children in the family, with the time spent by children on home assignments and the number of devices per family member. It was demonstrated that mothers lived through this period more easily than fathers. We found that the parents with a PhD degree provided the most effective support. It could be assumed, that studies at higher education institutions require time management. Having learned this skill, parents with higher education know how to self-organize and teach their children the same. Then, if our schools switch to remote teaching even partially, special guidelines with step-by-step explanations of the material shall be developed for parents. Furthermore, online counselling can be arranged for parents to present the course structure and the sequence of educational activities.